Blended Grammar Instruction via LMS and Peer Teaching in EFL Classrooms - Widari, IGA; Jazadi, Iwan; Pratiwi, Dirgahayu; Amri, Samsun; Jalaluddin, Jalaluddin (CV Sinergi Ilmu dan Publikasi, 2025)
This mixed-methods study investigates implementing a blended grammar instruction model that integrates LMS-based formative quizzes and student-led peer presentations within a lesson study framework in an Indonesian teacher education context. Drawing on mastery learning, sociocultural theory, and cognitive load principles, the study examines how this approach impacts student grammar mastery, perceptions, and instructor workload. The research employed quantitative analysis of student academic scores and Likert-scale survey data alongside qualitative insights from open-ended student reflections and instructor logs to enable triangulation of findings. Participants included 12 pre-service English teachers and three instructors in a semester-long Advanced English Structure course. Results show substantial gains in grammar performance, especially on cumulative assessments, and high student engagement with both LMS and peer learning components. Students valued repeated quiz practice, structured feedback, and collaborative presentations. Instructors reported reduced grading fatigue and increased pedagogical focus through LMS automation and team-based lesson study. Despite minor challenges in digital access and learner consistency, the model proved pedagogically effective and operationally sustainable. Findings affirm blended grammar instruction's relevance for enhancing student learning and instructional resilience in resource-constrained EFL settings.